Une schola monumentale découverte boulevard Frédéric-Latouche à Augustodunum/Autun (Saône-et-Loire) - Yannick Labaune; Antoine Louis; Véronique Brunet-Gaston; Anne Delor-Ahü; Jean-Pierre Garcia; Antony Hostein; Michel Kasprzyk (Gallia)
In 2011, an archaeological evaluation was carried out in the centre of the Roman city of Augustodunum (Autun) on a plot of over 1 ha. This operation afforded the opportunity to explore parts of two insulae along the main street, the so-called cardo maximus, an area that has benefited from recent advances in knowledge. The first insula hosts a high-status domus strongly resembling those of “Balbius Iassus” and the “Étui d’Or”, excavated in the vicinity in the 1970s; the second, addressed in this paper, contains the remains of a vast monumental complex covering approximately 900 m2. Most probably built at the beginning of the 2nd c. on the ruins of earlier houses, it was thoroughly restructured at the end of the 3rd c. or the beginning of the 4th and seems to have been abandoned then partly dismantled from the start of the 5th c. To judge by its plan and its situation within a residential area located in the immediate vicinity of the monumental centre, the building of the beginning of the late-antique period exhibits the functional and topographical features of a schola of exceptional size. Comparison with literary sources would seem to indicate that the remains are those of the scholae Maenianae, known from a speech delivered in AD 298 by Eumenius, a local notable, in the presence of the governor of Gallia Lugdunensis. Only further excavation and the discovery of an inscription could definitively prove this initial hypothesis. The discovery of such a vast complex, whatever function is assigned to it, vividly illustrates the importance of the monumental equipment of Autun under the Early Empire as well as the restoration work that took place in the city at the turn of the 300s.